REALISASI TEKNIK PENGEREMAN DINAMIK (DYNAMIC BRAKING) UNTUK MOTOR INDUKSI TIGA FASE MENGGUNAKAN ARDUINO UNO - Aris Widyatmoko; Ida Bagus Fery Citarsa; I Nyoman Wahyu Satiawan (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2017)
Three-phase induction motors are widely used by the industry because of several advantages, those are simple, inexpensive and easy maintenance. On the use of an induction motor is often required rapid braking process. Braking system to stop the rotation of an induction motor can be designed dynamically by creating a stationary motor magnetic field. Dynamic braking system can be done with enem circuit model, it will be injected with a direct current (DC). The purpose of this research is to know the characteristics of the dynamic braking circuit model with an Arduino UNO. The research was conducted by making the hardware systems which is used in the process of changing the stator circuit model, and software system with Matlab as an interface program to display the measurement parameters such as voltage , current and speed . Data collection was performed by injecting a DC current in each braking circuit. Braking parameters are then displayed graphically in Matlab interface. The results of this research are in braking star configuration, the fastest braking contained in the configuration 3 for 0, 35 seconds during no-load time, and load time of 0,2 seconds on. In a triangle configuration, the fastest braking contained in the configuration 2 for 0.4 seconds during no-load time, and load time contained in the configuration 5 and 6 for 0.17 seconds.